On the potential applications of acoustic emission in friction stir welding. (March 2022) - Ambrosio, D.; Dessein, G.; Wagner, V.; Yahiaoui, M.; Paris, J.-Y.; Fazzini, M.; Cahuc, O.
Abstract: In friction stir welding (FSW), only a few studies related to acoustic emission (AE) signals analysis have been conducted. In this work, the potential application of AEs in FSW is explored from a phenomenological and monitoring point of view. In static tests, with the tool only rotating without advancing, the information hidden behind AEs concerning the tool-workpiece interaction was investigated. Additionally, the sensors' positioning analysis is considered by comparing the signals' features obtained by placing the sensor on the welding plate or the support. Then in the second part, the effective capability of detecting internal defects during friction stir welding through AE signals monitoring is addressed. The experimental tests were performed on aluminum alloys of two different heat treatable families. Differences in the material plastic behavior depending on the aluminum alloys and the rotational speed were revealed by AEs features such as the amplitude and the absolute energy. In addition, internal defect occurrence was correlated with a shift in the signal centroid frequency. The results are auspicious for employing AE signals to deepen the tool-workpiece interaction and identify internal defects. Graphical abstract: Unlabelled Image Highlights: By increasing the rotational speed, tool-workpiece interaction changes from cold sliding to sticking to hot sliding. Modifications in acoustic emission features related to tool-workpiece interactions were revealed. Acoustic emission sensors can be placed on the support without losing information due to the positioning. The centroid frequency is the acoustic emission characteristic capable of identifying hot internal defects